Necrotizing pneumonia and purulent meningitis caused by bloodstream infection of CA-MRSA in a child: A rare case report - Li, Peng; Dai, Lizhong; Yuan, Ke; Song, Chunlan; Cheng, Yibing; Jing, Yu; Chen, Na; Cui, Junhao; Wang, Yangji; Fu, Shuqin (Frontiers in Pediatrics, 2022)
Case presentation We report the case of a girl aged 2 years and 10 months who had fever for 2 days, vomiting, poor mental status for 1 day, and one episode of convulsions. Symptoms and signs The patient experienced a rapid onset of symptoms with fever, vomiting, and convulsions. Upon physical examination on admission, she presented with the following: temperature 38.6°C; pulse 185 beats/min; respiration 49 beats/min; blood pressure 89/51 mmHg; drowsiness; piebald skin all over her body; rice-grain-sized pustular rashes scattered on the front chest and both lower limbs, protruding from the surface of the skin; bilateral pupils that were equal in size and a circle with a diameter of about 3.0 mm, and slow light reflex; cyanotic lips; shortness of breath; positive for the three-concave sign; a small amount of phlegm that could be heard in both lungs; capillary refill time of 5 s; cold extremities; and a positive Babinski sign. Diagnostic method A chest computed tomography scan showed multiple nodular and flake-like high-density shadows of varying sizes in each lobe in bilateral lungs, and a cavity with blurred edges could be seen in some nodules. A cranial magnetic resonance imaging examination demonstrated that the hyperintensity of diffusion-weighted imaging could be observed on the left cerebellar hemisphere and left parietal blade. Blood cultures, sputum, cerebrospinal fluid, and bronchoalveolar lavage fluid (BALF) by fiberoptic bronchoscopy all indicated the growth of methicillin-resistant Staphylococcus aureus (MRSA). Treatment methods After admission, the child was given meropenem combined with vancomycin, cefoperazone sulbactam combined with rifamycin, linezolid (oral) for anti-infection successively, and other adjuvant therapies. Clinical outcomes The patient recovered clinically and was discharged from our hospital. Recommended readers Neurology; Respiratory Medicine; Infectious Diseases Department.